Multicriteria decision‐making taxonomy for DevOps challenging factors using analytical hierarchy process. Issue 10 (22nd April 2020) - Khan, Arif Ali; Shameem, Mohammad
Abstract: Development and operations (DevOps) practices significantly accelerate and automate the continuous delivery and deployment of software systems. However, adopting DevOps concepts is not a straightforward job. Most organizations are not able to keep pace with the rhythm of continuous delivery and deployment, which are key DevOps attributes. Despite the significance of DevOps programs, it is still unknown why software development firms are demotivated or unable to adopt them. We tried to fill this gap by investigating, prioritizing, and developing the taxonomy of the key factors that could impact the adaptation and implementation of DevOps practices. We extracted a total of 16 factors from the available literature and empirically assessed them using the survey approach. The identified factors are further classified into three core categories of the software process improvement (SPI) manifesto. The analytical hierarchy process (AHP) approach was used to calculate the prioritization weight for each factor and present it as a taxonomy. The developed taxonomy provides a roadmap to tackle the key challenges to implementing DevOps and offers suggestions for streamlining DevOps practices.